Mobilizing mutations : human genetics in the age of patient advocacy - Navon, Daniel (University of Chicago Press, 2019)
With every passing year, more and more people learn that they or their young or unborn children carries a genetic mutation. But what does this mean for the way we understand a person? Today, genetic mutations are being used to diagnose novel conditions like the XYY, Fragile X, NGLY1 mutation, and 22q11.2 Deletion syndromes, carving out rich new categories of human disease and difference. Daniel Navon calls this form of categorization "genomic designation," and in Mobilizing Mutations he shows how mutations, and the social factors that surround them, are reshaping human classification. Drawing on a wealth of fieldwork and historical material, Navon presents a sociological account of the ways genetic mutations have been mobilized and transformed in the sixty years since it became possible to see abnormal human genomes, providing a new vista onto the myriad ways contemporary genetic testing can transform people's lives. Taking us inside these shifting worlds of research and advocacy over the last half century, Navon reveals the ways in which knowledge about genetic mutations can redefine what it means to be ill, different, and ultimately, human.
Keywords: Human chromosome abnormalities.; Medical genetics.; Human genetics.; Mutation (Biology); Genetic disorders.; Mutation; Genetic Diseases, Inborn; Genetic Services; Human Genetics -- methods; Genetics, Medical; Chromosomes humains -- Anomalies.; Génétique médicale.; Génétique humaine.; Mutation (Biologie); Maladies génétiques.; MEDICAL -- General.; Genetic disorders; Human chromosome abnormalities; Human genetics; Medical genetics; Electronic books.